Estudo do processo de reparo de enxerto ósseo em bloco submetido ao recobrimento com etil-cianoacrilato: análise histométrica e imunoistoquímica em ratos - Almeida, Rafael Santiago de [UNESP] (2015)
Objectives: Through histometric and immunohistochemical study, this study aimed to study the autograft repair process cranial cap of rats when subjected to coating with a cyanoacrylate layer on its surface. Material and Methods: 24 rats, adults were divided into two groups: Group I (n = 12): animals submitted to bone graft block fixed with drops of ethyl cyanoacrylate on its edges; Group II (n = 12): animals submitted to graft block fixed with drops of ethyl cyanoacrylate adhesive and covered with a layer of 200μL of ethyl-cyanoacrylate. The animals were sacrificed after 30 and 60 days postoperatively. The analysis was performed using the histometric analysis by hematoxylin and eosin in order to verify the bone resorption rates. The immunohistochemical analysis by immunostaining through the RANK-L and TRAP antibodies were conducted to verify the activity of osteoclasts and osteoblasts. The data were submitted to the Kruskal-Wallis test, with significance level of 5%. Results: The results showed no difference in the repair of bone graft covered or not with cyanoacrylate. Immunohistochemical analysis showed that the group with membrane showed moderate labeling for RANK-L and TRAP both within 30 as 60 days. Already in 30 days without membrane group to RANK-L protein was lightweight markup, but was to TRAP was moderate. And in the group without 60 days the membrane RANK-L protein and TRAP are presented lightly, therefore reducing training 11 and osteoblastic activity. Conclusions: The results show that the glue did not fulfill the requirements for guided tissue regeneration. However, future studies with methodological variations could bring additional and more conclusive results on the use of ethyl cyanoacrylate as a membrane barrier